Internal Auditing Outsourcing, Nonaudit Services and Audit Fees - Abdul Wahab, Effiezal; Gist, Willie E; Gul, Ferdinand A; Mat Zain, Mazlina (American Accounting Association, 2021)
This study examines the relationship between outsourced internal audits, nonaudit services and audit fees. We use Malaysian data to show that client firms that outsource their internal auditing function (IAF) are associated with lower external audit fees than those with in-house IAF. Moreover, this negative relationship is significantly stronger for firms that purchase greater amounts of nonaudit services (NAS) from the auditor. The results suggest that an auditor who provides NAS to a client and thus earns additional overall revenue is willing to accept lower audit fees provided a high audit quality can be achieved through reliance on outsourced IAFs.